Mathematics Learning with Scramble Model and Snakes and Ladders Media: Pembelajaran Matematika dengan Model Scramble dan Media Ular Tangga - Sri Rahmadhani; Puput Wahyu Hidayat; Sundahry (Academia Open, 2025)
General Background: Mathematics learning in elementary schools often fails to engage students, leading to low motivation and unsatisfactory outcomes. Specific Background: At SDN 71/II Sungai Gambir, fourth-grade students showed limited participation and low test scores in mathematics, particularly in fractions. Knowledge Gap: Traditional methods often overlook playful and interactive approaches that align with students’ cognitive and social needs. Aims: This study examined the application of the Scramble learning model supported by Snakes and Ladders media to strengthen mathematics learning among fourth-grade students. Results: Conducted through Classroom Action Research across two cycles, findings revealed progress in teacher performance (77.27% to 90.90%), student participation (65% to 85%), and test achievement (55% to 80%). Novelty: The integration of game-based media with a cooperative Scramble model demonstrated a unique strategy for fostering active, enjoyable, and meaningful mathematics learning in elementary settings. Implications: These findings suggest that teachers may adopt interactive and playful methods to improve classroom dynamics, strengthen student collaboration, and achieve better mathematics learning results. Highlight: Improved teacher performance, student participation, and test scores. Scramble model combined with Snakes and Ladders created active and fun learning. Results show mathematics learning became more meaningful and engaging. Keywords: Scramble Learning Model, Snakes and Ladders, Mathematics Learning, Student Participation, Elementary Education